Psychological interventions for inflammatory bowel disease: a systematic review and component network meta-analysis protocol. Issue 6 (22nd June 2022) - Tiles-Sar, Natalia; Neuser, Johanna; de Sordi, Dominik; Rücker, Gerta; Baltes, Anne; Preiss, Jan; Moser, Gabriele; Timmer, Antje
Abstract : Introduction: Patients with inflammatory bowel diseases (IBD) often report psychological problems, unemployment, disability, sick leave and compromised quality of life. The effect of psychological interventions on health-related outcomes in IBD is controversial as previous reviews faced the obstacle of high heterogeneity among provided multimodular interventions. The heterogeneity can be addressed with network meta-analysis (NMA) and (multi)component NMA (CNMA). We aim to investigate whether psychological interventions can improve quality of life, clinical and social outcomes in IBD using NMA and CNMA. This is the study protocol. Methods and analysis: We will consider randomised, quasi-randomised and non-randomised controlled trials, including cluster randomised and cross-over trials with 2 months of minimum follow-up. The conditions to be studied comprise Crohn's disease and ulcerative colitis in children, adolescents and adults. We will include any psychological intervention aiming to change the health status of the study participant. We will search Medline, Embase, Web of Science, CENTRAL, LILACS, Psyndex, PsycINFO, Google Scholar and trial registries from inception (the search will be updated before the review completion). Two authors will independently screen all references based on titles and abstracts. For data extraction, standard forms are developed and tested before extraction. All information will be assessed independently by at least two reviewers, and disagreements solved by consensus discussion or a third rater if necessary. The data synthesis will include a pairwise meta-analysis supported by meta-regression. We will conduct NMA (all treatments will constitute single nodes of the network) and CNMA (we will define all treatments as sums of core components, eg, cognitive +behaviour, or cognitive +behaviour + relaxation, and additionally consider interactions) using the R Package netmeta. Ethics and dissemination: No ethical approval is required. Reports will include the final report to the funder, conference presentation, peer-reviewed publication and a patient report. PROSPERO registration number: CRD42021250446.